PEMETAAN POTENSI DESA WISATA DENGAN SISTEM INFORMASI GEOGRAFIS DI PULAU PRAMUKA, KEPULAUAN SERIBU - Aryuliani, Shavira (Jurnal Pariwisata PaRAMA : Panorama, Recreation, Accomodation, Merchandise, Accessbility, 2025)
Rural tourism is a form of tourism that is increasingly attractive and is becoming a world trend that can achieve government goals in encouraging regional development and people's welfare. Pramuka Island is one of the tourist destinations that has a high level of visits and is one of the tourist villages included in the Kemenparekraf program which is in the pilot category. This study aims to map the potential of tourist villages on Pramuka Island, Seribu Islands with three categories, namely attractions, amenities, and accessibility. This study uses a qualitative descriptive method with a spatial approach, this study utilizes primary data from field observations, as well as secondary data from literature studies on the internet. Identification of the potential of tourist villages begins with mapping using QGIS software which produces a map of attractions, amenities, and accessibility of Pramuka Island Tourism Village. This study resulted in the identification of the potential of Pramuka Island Tourism Village based on the three categories. In the attraction category, Pramuka Island as a Tourism Village has various types of tourist attractions such as marine tourism, educational tourism for planting mangrove seedlings and coral transplantation, and the beauty of the sunrise beach. Based on the amenity category, there are 18 accommodations and 14 supporting facilities for tourism activities. The research results show that there are 2 accesses to the Pramuka Island Tourism Village that can be reached by sea, namely Muara Angke Port and Marina Ancol Port.